ENHANCING ENGLISH SPEAKING SKILLS THROUGH TASK- TEACHING AMONG UZBEK LEARNERS - Zokirova Marjona Xislatjon qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This research explores the effectiveness of task-based teaching (TBT) in improving English speaking skills among Uzbek learners. It analyzes how communicative tasks, such as role-plays, discussions, and problem-solving activities, enhance learners' fluency, accuracy, and confidence in spoken English. The study is based on classroom observations, learner feedback, and assessment results from English language courses in Uzbekistan. The findings suggest that integrating real-life communicative tasks significantly boosts learners' motivation and speaking performance, making TBT a practical and engaging approach for English language instruction.